Intelligent neuro-system solution - Wan Hasan, Wan Zuha (Universiti Putra Malaysia Press, 2016)
Brain is an organ that serves as the center of the nervous system containing soft nervous tissue in the skull of vertebrates. Physiologically, the function of the brain is to coordinate the centre of sensation, intellectual capacity and neuronal activity. Today, knowledge of intricacies and potentials of human brain has inspired many manufacturers to produce similar intelligent systems that can be applied into specific applications in medical engineering to benefit mankind.